2015
DOI: 10.1051/0004-6361/201526119
|View full text |Cite
|
Sign up to set email alerts
|

(50000) Quaoar: Surface composition variability

Abstract: Aims. The goal of this work is to investigate the composition of the surface of (50000) Quaoar and its spatial variability. Methods. We present new continuous spectra from the visible to near-IR (0.3−2.3 μm) obtained with the X-Shooter instrument at the VLT-ESO at four different epochs on the surface of Quaoar. The data represent the highest spectral resolution data ever obtained for this object and the first near-IR dataset acquired in a single exposure over the entire wavelength range. They are complemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…This identification is not firm because most of the absorption bands of ethane ice are located in spectral regions dominated by CH 4 absorption and the observed features are weak Sasaki et al, 2005;Cruikshank et al, 2006;DeMeo et al, 2010;Merlin et al, 2010;Holler et al, 2014 ). It should be noted that C 2 H 6 has also been tentatively identified on the KBO 50,0 0 0 Quaoar ( Dalle Ore et al, 2009;Barucci et al, 2015 ). Species expected to arise from N 2 :CH 4 photochemistry, such as C 2 H 2 , C 4 H 2 , HC 3 N and HCN, have not been detected.…”
Section: Introductionmentioning
confidence: 99%
“…This identification is not firm because most of the absorption bands of ethane ice are located in spectral regions dominated by CH 4 absorption and the observed features are weak Sasaki et al, 2005;Cruikshank et al, 2006;DeMeo et al, 2010;Merlin et al, 2010;Holler et al, 2014 ). It should be noted that C 2 H 6 has also been tentatively identified on the KBO 50,0 0 0 Quaoar ( Dalle Ore et al, 2009;Barucci et al, 2015 ). Species expected to arise from N 2 :CH 4 photochemistry, such as C 2 H 2 , C 4 H 2 , HC 3 N and HCN, have not been detected.…”
Section: Introductionmentioning
confidence: 99%
“…This fact can be an indication that other KBOs with sizes comparable to Pluto could also present recent geological activity. One example of this possibility is the potential presence of cryovolcanism in Quaoar (Barucci et al 2015). However, due to the large distance of the KBOs from the Sun, observational data were not enough to significantly improve our knowledge about these bodies, to carry out comparative planetology.…”
Section: Introductionmentioning
confidence: 99%
“…The rotational period is approximately 8.84 h, and it has one known satellite (Weywot, about 80 km in size). The best compositional model obtained so far (Barucci et al 2015) reported a surface made of crystalline water ice, methane, as well as ethane, nitrogen, organic materials, and possibly ammonia water. The presence of high volatile material such as ammonia water and nitrogen suggests that the surface of Quaoar may be relatively young and shaped by an efficient renewal mechanism.…”
Section: Quaoarmentioning
confidence: 99%